The 2022 population census in Serbia: sociopolitical context and methodological innovations - Vasić, Petar (Sociološki pregled, 2023)
Since the first modern census was conducted in Serbia in 1866, 20 censuses have been conducted to date. However, controversy regarding the field research, structure of questions and use of data has never been stronger. The sociopolitical context, in other European countries alike, that preceded the 2022 census was marked by low-key invitations from government representatives to participate in the Census, an inconspicuous campaign by the Statistical Office of the Republic of Serbia, conspiracy theories on disseminated social networks and calls for a boycott. On the other hand, despite methodological improvements, the census was marked by implementation problems, untrained enumerators, lack of manpower in the field, and the imputation from administrative sources of persons who did not participate in the Census. It seems that this time some of major causes of field research problems and, once again, methodological incompatibilities with previous censuses, were the inadequate communication with the public and insufficient training levels of enumerators.